Reindeer grazing controls willows but has only minor effects on plant communities in Fennoscandian oroarctic mires. Issue 1 (1st January 2019) - Kolari, Tiina H. M.; Kumpula, Timo; Verdonen, Mariana; Forbes, Bruce C.; Tahvanainen, Teemu
ABSTRACT: Shrubification of arctic tundra is a well-recognized phenomenon, and it can be particularly rapid in moist habitats. Reindeer grazing can inhibit shrubification, but grazing impacts on mire vegetation have been overlooked. We studied grazing effects on plant communities and Salix lapponum in oroarctic mires at the border of Finland and Norway. We compared plant community structure and S. lapponum abundance and traits between (1) grazed fens (Finland); (2) experimental exclosures (Finland), where reindeer have been kept out for 13 years; and (3) nongrazed fens (Norway). Grazing effect on shrubification was assessed using the Normalized Difference Vegetation Index (NDVI) and leaf area index (LAI). We did not find a uniform direction of vegetation change connected to the exclosure treatment, and grazing treatments were overlapping in multivariate ordination. Neither NDVI nor LAI indicated clear differences. Instead, significant results were revealed in total abundance of species groups and in S. lapponum traits. The cover of bryophytes was significantly lower under free grazing. Reindeer grazing reduced the abundance, height, and flowering and increased leaf N concentration of S. lapponum . We conclude that reindeer grazing controls willows and affects total abundance of important species groups, and plant community structure is resistant to grazing effects in oroarctic mires.